Integration of Augmented Reality in Anatomy Learning : Innovation in Health Education - Alfina Camellia (International Journal of Health and Medicine, 2025)
The development of digital technology brings great opportunities in the world of education, especially in the health sector. Augmented Reality (AR) is one of the technological innovations that is able to integrate virtual objects into the real environment in real-time, providing a more immersive and interactive learning experience. This article aims to explore the integration of AR in anatomy learning based on literature studies from international journals. Using a qualitative approach based on literature studies, this study examines various findings from foreign scientific journals regarding the effectiveness, challenges, and potential of using AR in anatomy education. The results of the study show that AR is able to improve students' visual understanding, learning engagement, and information retention. However, there are also challenges in terms of development costs, technology access, and teacher readiness. AR has great potential as a medium for anatomy learning in the digital era, but its implementation requires adequate infrastructure and training support.